The Role of Type II Fatty Acid Synthesis Enzymes FabZ, ODSCI, and ODSCII in the Pathogenesis of Toxoplasma gondii Infection - Xu, Xiao-Pei; Elsheikha, Hany M.; Liu, Wen-Ge; Zhang, Zhi-Wei; Sun, Li-Xiu; Liang, Qin-Li; Song, Ming-Xin; Zhu, Xing-Quan (Frontiers in Microbiology, 2021)
Toxoplasma gondii is an obligate intracellular protozoan parasite, which has a worldwide distribution and can infect a large number of warm-blooded animals and humans. T. gondii must colonize and proliferate inside the host cells in order to maintain its own survival, while securing essential nutrients for the development of the newly generated tachyzoites. The type II fatty acid biosynthesis pathway (FASII) in the apicoplast is essential for the growth and survival of T. gondii. We investigated whether deletion of genes in the FASII pathway influences the in vitro growth and in vivo virulence of T. gondii. We focused on beta-hydroxyacyl-acyl carrier protein dehydratase (FabZ) and oxidoreductase, short chain dehydrogenase/reductase family proteins ODSCI and ODSCII. We constructed T. gondii strains deficient in FabZ, ODSCI and ODSCII using CRISPR-Cas9 gene editing technology. The results of immunofluorescence assay, plaque assay, proliferation assay and egress assay showed that in ΔFabZ strain the apicoplast was partly lost and the growth ability of the parasite in vitro was significantly inhibited, while for ΔODSCI and ΔODSCII mutant strains no similar changes were detected. RHΔFabZ exhibited reduced virulence for mice compared with RHΔODSCI and RHΔODSCII, as shown by the improved survival rate. Deletion of FabZ in the PRU strain significantly decreased the brain cyst burden in mice compared with PRUΔODSCI and PRUΔODSCII. Collectively, these findings suggest that FabZ contributes to the growth and virulence of T. gondii, while ODSCI and ODSCII do not contribute to these traits.